Pendampingan Penyusunan Laporan Keuangan Guna Peningkatan Akuntabilitas Pada Koperasi Mitra Sejahtera - Ari Sita Nastiti; Budi Santoso (Journal of Community Development, 2023)
Multi-business Cooperative Partners (KSU) Mitra Sejahtera is a cooperative that was established in 2015 and operates their business at the Integrated Islamic Middle School (SMPIT) Jember. Partners have various business units. Some of the problems experienced by Partners, among others: do not have an understanding of cooperative accounting and the cooperative's financial reports have not been prepared so that Partners cannot hold RAT. Based on the problems and priorities of the Partners, the solution offered is assistance in preparing financial reports to increase accountability. This PKM activities take place from January to May 2023 using the Participatory Learning and Action (PLA) method, which emphasizes the principle of learning by doing. The stages of implementing this PKM activity begin with the preparation stage, collecting financial data, delivering material, assisting the process of preparing financial reports and ending with the evaluation stage. Based on the evaluation results, the cooperative's financial reports have been compiled so that the RAT can be implemented. However, partners' understanding of accounting and the preparation of cooperative financial reports still needs to be improved.